รูปแบบการสร้างสรรค์นาฏยประดิษฐ์อีสานกับสถาบันอุดมศึกษา - มุสิกา คำล่า (วารสารศิลปศาสตร์ มหาวิทยาลัยอุบลราชธานี, 2016)
รูปแบบแนวความคิดการสร้างสรรค์นาฏยประดิษฐ์อีสานนี้ ได้นำผลจากวิทยานิพนธ์เรื่อง แนวความคิดการสร้างสรรค์นาฏยประดิษฐ์อีสานในวงโปงลาง ดุษฎีนิพนธ์สาขานาฏยศิลป์ไทย คณะศิลปกรรมศาสตร์ จุฬาลงกรณ์มหาวิทยาลัย มาเขียนเป็นบทความทางวิชาการเพื่อเผยแพร่ สถาบันอุดมศึกษามีพันธะกิจด้านการเรียนการสอน การวิจัย การบริการวิชาการ และการทำนุบำรุงศิลปวัฒนธรรม ซึ่งการทำนุบำรุงศิลปวัฒนธรรมนี้ ได้ดำเนินการทั้งภายนอกมหาวิทยาลัยและภายในมหาวิทยาลัย ซึ่งภายในมหาวิทยาลัยได้มีการส่งเสริมให้นักศึกษาจัดตั้งชมรมและชุมนุมที่เกี่ยวข้องโดยตรง เช่น ชมรมนาฏศิลป์และดนตรี ชมรมศิลปะการแสดง เพื่อให้นักศึกษาที่มีความสนใจได้ร่วมทำกิจกรรมเพื่อเป็นการอนุรักษ์ สืบสาน และฟื้นฟู ศิลปะการแสดง ในปัจจุบันพบว่ามีสถาบันอุดมศึกษาที่จัดการเรียนการสอนด้านนาฏยศิลป์เพิ่มมากขึ้น ทั้งในระดับปริญญาตรีจนถึงระดับบัณฑิตศึกษา โดยเฉพาะสาขานาฏศิลป์พื้นบ้านอีสาน ได้เปิดทำการเรียนการสอนโดยแต่ละแห่งมีการสร้างสรรค์นาฏยประดิษฐ์อีสาน เพื่อการเรียนการสอนและการวิจัยเกิดขึ้นเป็นประจำ จึงควรมีการนำเอารูปแบบแนวความคิดการสร้างสรรค์นาฏยประดิษฐ์อีสานในวงโปงลางที่วิจัยและพัฒนาขึ้นนี้ไปใช้ เพื่อยกระดับการแสดงอีสานในแง่ของผลงานสร้างสรรค์เชิงวิชาการ ซึ่งต้องอาศัยกรอบแนวความคิดที่เป็นระบบระเบียบอย่างชัดเจน ในอีกด้านหนึ่งสถาบันการศึกษาจะต้องผลิตบัณฑิตที่จะจบไปเป็นนักนาฏยประดิษฐ์ที่มีความรู้ความสามารถในการสร้างสรรค์นาฏยประดิษฐ์อีสาน ซึ่งจะเป็นผู้นำในการสืบสานและพัฒนาศิลปะการแสดงแขนงนี้ The concept of Northeast Thai dance choreography written in this academic work comes from “Northeast Dance Choreography for Ponglang Band,” a thesis produced by a student of Thai Classical Dances Major in the Faculty of Performing Arts, Chulalongkorn University. Some of the content in the thesis was selected and rewritten in the form of academic article in order to publicize it to the society. The missions of any higher education institute consist of providing learning activities, research, academic services, and conserving/supporting art and culture. Higher education institute operate inside and outside themselves in order to accomplish these missions. Internal activities include encouraging students to set up and participate in various clubs directly related to this field, such as Music and Performing Art Club, Acting Club, etc. The purpose of this is to provide opportunities for students to do activities that conserve, continue and restore performing arts. In the present, many higher education institutes offer courses in performing arts in both graduate and post-graduate programs. For Northeast Thai Dances in particular, choreography is also included in the program. It is practical to apply the concepts and forms of Northeast Thai dance choreography for ponglang band, which have already been researched and developed, with other learning activities and academic work. Doing so will elevate Thai Northeast performing art in terms of academic creative work, which requires systematic conceptual framework. In addition, the institutes will be able to produce graduates who will become proficient choreographers of Thai Northeast Dance, and leaders in the development and conservation of this field of traditional performing art.